Factors Affecting Performance: Jordanian Hospitality Employees as a Case Study - AL- MKHADMEH, Ahmad A.; SHATNAWI, Hakam S.; ALANANZEH, Omar; MASA’DEH, Ra’ed (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
Hospitality institutions such as hotels and restaurants realize the importance of the performance of the human capital in their success, development, and market position. Thus, this research is conducted to identify the factors impacting Jordan's hospitality employee performance. Therefore, Leadership, post COVID-19 practices, Organizational Culture, and Employee Reaction to Changes are the factors that have been measured to explore their impact on employee performance. An online questionnaire was utilized and distributed to the study sample. The random sample technique was used, and 219 responses were obtained. The findings revealed that the aforementioned factors were shown to have a significant effect on the performance of employees. The findings also reveal that the new safety practices have had a significant impact on Jordanian employees' performance.